1969
DOI: 10.1149/1.2411820
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Pipes in Silicon NPN Structures

Abstract: Diffusion pipes in silicon NPN structures were investigated both by electrical measurements and by microsectioning. It was found that certain crystalline defects, specifically stacking faults and edge dislocations, can act as sites for the formation of such pipes. The presence of gold doping at these lattice defects greatly increases the incidence of pipes, apparently by offering a path of enhanced diffusivity for phosphorus from the emitter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1972
1972
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 2 publications
0
19
0
1
Order By: Relevance
“…[112][113][114]120 The large number of variables noted above also contributed to the significant variability of carrier lifetime with the ''same'' dislocation density …”
Section: -114mentioning
confidence: 99%
See 1 more Smart Citation
“…[112][113][114]120 The large number of variables noted above also contributed to the significant variability of carrier lifetime with the ''same'' dislocation density …”
Section: -114mentioning
confidence: 99%
“…In a related manner, the emitter-collector leakage in narrow-base devices was shown by Fred Barson and colleagues to result from the enhanced emitter dopant diffusion along dislocations threading the emitter and collector of a transistor ͑pipes͒, which resulted in electrical shorts. [112][113][114] The degradation of gain, increased noise of PNP transistors, and increased transistor second breakdown as well as related effects in the degradation of p-n junction characteristics due to hydrostatic pressure, uniaxial stress, anisotropic stress, mechanical damage and other structural defects have also been summarized. 1 The recovery of p-n junction characteristics due to thermal processing and the beneficial effects of gettering procedures by Goetzberger and Shockey on device 115 and Michael Poponiak and colleagues IC characteristics 116 were also observed.…”
Section: Plastic Deformation In Siliconmentioning
confidence: 99%
“…Such pipes were found only under the phosphorus-diffused emitter areas and not in the remainder of the base area. This suggested a model that the pipes are a result of enhanced phosphorus diffusion along crystalline defects (4). The addition of gold increases the junction leakage suggesting that the precipitation of gold or other fast diffusers on the defects passing through the collector-base junction m a y also play a significant role (5).…”
Section: Diffusion Into Ion Implanted Surfacesmentioning
confidence: 99%
“…It has been reported that RP silicon epitaxy has more advantage in characteristics of layer [autodoping, pattern shift, and uniformity of epitaxial layer, etc. (1)(2)(3)(4)(5)], than those of .atmospheric silicon epitaxy.…”
Section: Introductionmentioning
confidence: 99%